Effect of fat aggregate size and percentage on the melting properties of ice cream. (October 2022) - Liu, Xiangyu; Sala, Guido; Scholten, Elke
Graphical abstract: Highlights: The melting behavior of ice cream was related to the stability of the fat network. Fat destabilization had a larger effect on melting properties than fat content. Melting lag time was related to fat aggregate size. Total melting time and percentage were related to the fat aggregate percentage. A critical fat aggregate size was found to be related to the lamellae thickness. Abstract: In this study, we investigated the effect of fat aggregate size and percentage on fat network formation and, ultimately, on the melting properties of ice cream. To control fat destabilization degree and fat network formation, we varied fat and emulsifier content, and blended coconut oil with milk fat, obtaining three different sample series varying in: 1) fat content, 2) fat aggregate size, and 3) fat aggregate percentage. The degree of fat destabilization in terms of aggregate size and the percentage was measured by light scattering techniques. The distribution of the fat around the air cells and in the unfrozen serum phase was calculated based on the measured overrun. Overall, a similar overrun was found in the three series of ice cream. The fat percentage in the remaining phase was measured to verify how much fat and what type of fat aggregates were present in the fat network. The results show that fat destabilization degree is relatively more important than fat content in determining the melting behavior of ice cream with low overrun. Clear relations between different fat destabilization parameters and ice cream melting behavior were established, indicating that the melting behavior of ice cream is related to specific properties of the fat network. Controlling fat destabilization in the unfrozen ice cream phase may be used to alter the properties of ice cream, and could contribute as a fat reduction strategy in ice cream.